Um estudo do resumo acadêmico em curso de graduação - Teles, Maria Edleuza da Silveira (2007)
This essay inserts in the Line of Research reading, writing and teaching of Portuguese Language and has for objective to make a study on the academic summary. For in such way, we appeal to specialized literature to clarify concernments aspects to the conception of this literary sort, its characteristics and principles of elaboration. To the adopted theoretical beddings we articulate the analysis on the nineteen summaries produced for students from the forth semester of the Course of Letters of a particular college net of education in the capital of Sao Paulo, with the intention to verify summaries produced for academics where measured if they are in accord with the pointed principles of elaboration. As result of the inquiry, we evidenced that many of these principles are not yet part of the repertoire of knowledge the students and, probably, nor the professors. In complement to the made analyses, we consider possible didactic interventions that intend parameters for other actions. We believe that the considerations displayed in this research, even so if not deplete in itself, can contribute for the deepening of the reflections on this sort that has become, of certain form, essential in the practical academics